Synthesis and characterization of new alternating, amphiphilic, comblike copolymers of poly(ethylene oxide) macromonomer and N-phenylmaleimide - Cianga, L; Sarac, A; Ito, K; Yagci, Y (WILEY, 2005)
A surface-active p-vinyl benzyloxy-w-hydroxy-poly(ethylene oxide) macromonomer containing 22 pendant structural units of ethylene oxide (St-PEO22) was synthesized with an initiation method. Because of its solubility in a large variety of solvents, the free-radical copolymerization with electron-acceptor N-phenylnmaleimide (NPMI) was performed at 60 degreesC in benzene and tetrahydrofuran (THF) as isotropic media and in a water-THF mixture or water as a heterogeneous medium. Oil-soluble 2,2'-azobisisobutyronitrile and water-soluble 4,4'-azobis(4-cyanovaleric acid) were used as the initiators at fixed concentrations. Two different. St-PEO22/NPMI comonomer ratios (1/1 and 3/7) at a fixed total comonomer concentration in the polymerization system were used. The structures, compositions, and microstructure peculiarities of the obtained alternating, amphiphilic, comblike copolymers were determined by NMR analysis. For the copolymers synthesized in hydrophilic media, differential scanning calorimetry showed, near the endothermic peak attributed to the melting of the polyethylene oxide) side chains, the presence of a second peak due to the partially ordered phase that could exist between the crystalline state and the isotropic melt. Also, the thermal stability of the obtained copolymers was studied with thermogravimetric analysis. (C) 2004 Wiley Periodicals, Inc.
Keywords: amphiphiles; copolymerization; macromonomer; N-phenylmaleimide; poly(ethylene oxide); SURFACE-ACTIVE MONOMER; MALEIC-ANHYDRIDE; GRAFT-COPOLYMERS; PHENYL-MALEIMIDE; RADICAL COPOLYMERIZATION; SIDE-CHAINS; POLYMERIZATION; STYRENE; POLYMERS; DISPERSION; Polymer Science